Motivasi Dan Pengetahuan Relawan Tentang Penanggulangan Bencana - Widyastuti, Merina; Ambar Sari, Ninik; Jannah, Siti Nur; Anggoro, Sapto Dwi; Rustini, Sri Anik (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: High motivation to become a volunteer affects the effort given by someone to work. They involve themselves in disaster management activities that aim at the goal of helping and rescuing victims, as provisions for quick and precise rescue of victims, volunteers need disaster management knowledge so that the rescue of disaster victims is helped and the rescue achieves the desired goals. Objectives: Â The purpose of this study was to determine the relationship between motivation to become a volunteer and knowledge of disaster management in Surabaya. Methods: The research design was analytic observational with cross sectional approach. The sampling technique uses Probability Sampling using simple random sampling. The population of Surabaya volunteers with a sample technique using simple random sampling obtained a sample of 50 respondents. Instrument used a questionnaire. Data were analyzed using the Spearman Rho test with a degree of significance Ïâ‰¤ 0.05 Results: The results showed that most respondents had high motivation to become volunteers. Most respondents had a good level of knowledge related to disaster management. And obtained a relationship between motivation to become a volunteer and knowledge of disaster management in Surabaya. From the statistical results of the Spearman rho test, it shows the value of r = 0.357 with a value of p = 0.011 Conclusions: Â The implication of this research is that high motivation makes it easy for volunteers to learn about disaster management science and vice versa